Preparation technology and photoluminescence properties of CdTe nanocrystals in colloidal solutions and polymeric matrices - Kalytchuk, S.M.; Korbutyak, D.V.; Scherbak, L.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
An analysis of physical mechanisms responsible for the influence of stabilizer
type and ambient material on CdTe nanocrystal growth rate and passivation effectiveness
of surface dangling bonds has been carried out. The possibility to change properties of
nanocrystals by changing the stabilizer type has been shown.